Condamner et punir dans une ville moyenne de province au temps des Lumières : les exécutions publiques à Tours (1762-1768) - Fabrice Mauclair (Criminocorpus)
Taking place in the historical framework of the city of Tours (France) during the 1760s, the present study seeks to contribute to the recent and renewed questioning on hangmen, public executions, and the treatment of bodies by the criminal justices of the old regime. The choice of this location and of this period results from the discovery of an exceptional document: a statement written by an hangman to request the payment of his fees. This paper first analyses this invaluable source in its context, dealing more particularly with the unique personality of its author: the hangman Gilles-François-Nicolas Berger. Then it describes in detail the public executions ordered in Tours between 1762 and 1768: frequency and motives, criminals and crimes, material organization, rituals and participants. The study also tackles the use of torture and that of an “object” of recent interest to both archeologists and historians: the “patibulary forks”. As a general viewpoint, the paper seeks to rise new interrogations on the characteristics and evolutions of the criminal justice in a medium-sized town of province during the Enlightenment.